Body-mass index in adolescence and cardiovascular death in adulthood. - Dwyer, T; Sinaiko, A; Raitakari, O (Massachusetts Medical Society, 2016)
The finding by Twig et al. that a person’s BMI at 17 years of age is positively associated with the risk of cardiovascular death strengthens the evidence that risk factors in early life are related to the development of cardiovascular disease in adults. However, persons who are 17 years of age are more similar to young adults than to children. Thus, key questions remain unanswered relating to the earliest ages in childhood at which an increased risk of cardiovascular disease might be present and at which the risk factors for cardiovascular disease, either in association with or independent of obesity, are arbiters of identifiable cardiovascular disease in adults.